Religious Construction in Decision Making of Indonesian Customers for Financial Transactions on Syariah Banks - Pabbajah, Mustaqim; Widyanti, Ratri Nurina; Harun, Dato' Sudin; Darwis, Muh; Widyatmoko, Widi Fajar (Al-Albab, 2023)
This study aims to explain how Islamic concepts, symbols and values have implications for people. Especially when they must make decisions to make financial transactions in Islamic banking. Likewise, the religious trend accompanied by the spirit of city has resulted in the enthusiasm of the community to transact with institutions labelled religion in practice. Data collection used in this study was carried out by observation and distributing questionnaires to respondents (customers). Documentation studies are also conducted to find literature related to this study. There are three findings described in this study. First, the conception and symbol of religion is an essential element in the existence of Islamic banking in Indonesia. Second, the understanding of the religious community has been constructed in the decision to make economic transactions in Islamic banks. Third, the religious trend accompanied by religious zeal makes sharia banks in Indonesia have bright prospects to attract the interest of the public to transact. The enermous potential of Islamic banks in Indonesia will experience an increase if the religious values and symbols are implemented correctly and adequately. Religious construction of economic behaviour has resulted in a shift in the pattern of community transactions in the name of religion. This shift certainly provides not only positive expectations in the religious society, but also provides broad opportunities for the banking business world.